2001
DOI: 10.1046/j.1440-1703.2001.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in a grassland community: Use of power law

Abstract: A new regression analysis was proposed to evaluate the degree of spatial heterogeneity for individual species comprising a plant grassland community. The weighted average of the heterogeneity value of all the species comprising the community provides a measure of community‐level heterogeneity. A field survey was carried out, as an example, in order to analyze the spatial heterogeneity of a pasture with grazing cows, using 100 quadrats 50 cm × 50 cm, each of which was divided into four smaller quadrats 25 cm × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
0
36
0
4
Order By: Relevance
“…The (adjusted) power law (Madden and Hughes, 1995;Shiyomi et al, 2001) was applied to analyze the communitytype spatial heterogeneity. The sample mean and variance for community type i in a landscape are expressed as m i and v i , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The (adjusted) power law (Madden and Hughes, 1995;Shiyomi et al, 2001) was applied to analyze the communitytype spatial heterogeneity. The sample mean and variance for community type i in a landscape are expressed as m i and v i , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Shiyomi et al ( , 2001 and proposed simple methods to measure spatial heterogeneity that have been successfully applied to the analysis of grassland vegetation Wang et al, 2002;Yasuda et al, 2003;Shiyomi et al, 2004;Chen et al, 2005;Tsuiki et al, 2005;Chen et al, 2006) and landscape-scale analyses using vegetation and land-use maps (Huang et al, 2004;Hori et al, 2005;Song et al, 2005). Here, we used the power law (Madden and Hughes, 1995;Shiyomi et al, 2001) as a statistical model to determine the macro-scale spatial heterogeneity of vegetation within and among landscapes with special reference to water resources.…”
Section: Introductionmentioning
confidence: 99%
“…The power law was extended by Shiyomi et al (2001) to deal simultaneously with many plant species from a vegetation survey. Herein, we let the sample mean and sample variance for species i be expressed as m i and v i , respectively.…”
Section: Survey and Analysismentioning
confidence: 99%
“…Recent modeling studies have shown that the patch size distribution of arid and semiarid vegetation can be described using power law distributions (Ke´fi et al 2007a, Scanlon et al 2007) and that deviations from such patterns (e.g., from a power law to a truncated power law) could be used as an early-warning signal to monitor desertification processes (Ke´fi et al 2007a). These findings are appealing because power laws occur in other ecosystems (Shiyomi et al 2001, Sole´and Bascompte 2006, Bridges et al 2007) and because their use could represent a significant step toward the development of a sound and widely applicable desertification monitoring system. Despite their potential implications, the suggestions of these studies have not been widely validated, and it is largely unknown how variations in power laws are connected to ecosystem functioning and desertification processes under field conditions (Sole´2007).…”
Section: Introductionmentioning
confidence: 99%